The ability basic physical components of row athlete - Januar Inggar Yadi; Yudy Hendrayana (Nicolaus Copernicus University in Toruń, 2020)
The problem in this study is how the physical components of the paddle sport. The purpose of this study was to determine the ability level of the basic physical components of paddle athletes in West Kalimantan. The method used in this research is descriptive method with survey research form. The population in this study amounted to 18 athletes. The sample in this study amounted to 18 athletes. Based on the results of research conducted on the ability level of basic physical components, it turns out that paddle athletes in West Kalimantan belong to 4 categories: perfect amounted to 2 athletes or by 11%, either 7 athletes or 39%, good categories of 5 athletes or 28 % and enough amount to 4 athletes or by 22%. This shows that the ability of the basic physical components in West Kalimantan paddle athletes is in the good category.